Industrial training report: Unic Leisure Group Sdn Bhd - Abdul Rahim, Nur Alia Farhani (Universiti Teknologi MARA, Perlis, 2024)
This report outlines my six-month internship at Unic Leisure Group Sdn Bhd in Utan Aji, Perlis, which I completed to meet academic requirements for MGT 666 while also gaining practical job experience. As a financial trainee for Unic Maintenance, I was in charge of preparing supporting evidence for audits, managing UM's main account with Bank Islam, learning and implementing the full set of SQL accounting systems, and handling accounts for Go Bus Sdn. Bhd. and petty cash for construction projects. In addition, I ensured that financial data was accurately tracked and updated inside the SQL system. This internship program also provides extensive experience in understanding the complexities of a full set of accounts. This experience taught my critical thinking and practical accounting abilities while also teaching me how to manage emotions, communicate successfully with the head of department, and balance responsibilities through self-scheduling. The problems were tackled with increased organizational abilities and a proactive attitude to issue resolution, which strengthened my position within the company. Unic Leisure Group Sdn Bhd, a prominent bus sales and servicing company, also provides lorry, truck, and van repair. The encouraging workplace environment gave me the opportunity to explore and learn from practical activities, which enhanced my accounting knowledge and built my connections with coworkers and managers. This internship helped prepare me for future job opportunities by providing me with critical skills in filing, computer systems, and accounting procedures.